Maternal gut microbiome interventions to improve maternal and perinatal health outcomes: Target product profile expert consensus and pipeline analysis. - Kate Mills; Joelle Tan; Tahlia Guneratne; Lindsay Keir; Maya Goldstein; Cécile Ventola; Maureen Makama; Anne Ammerdorffer; A Metin Gülmezoglu; Joshua P Vogel; Annie R A McDougall (PLoS ONE, 2025)
Objective To develop a novel Target Product Profile (TPP) outlining the minimum and optimal requirements of probiotics targeting the maternal gut microbiome, create a research and development (R&D) pipeline of maternal microbiome interventions, and identify the highest potential probiotic candidates matching TPP criteria. Design A mixed-methods study including in-depth interviews, an international survey, and online public consultation, with systematic R&D pipeline development. Setting International research context in maternal gut microbiome interventions. Population Ten stakeholder groups were included in the study for feedback on the TPP development. Methods Stakeholder feedback from 23 interviews and 32 survey responses was analyzed to revise the TPP. A systematic search of databases (Adis Insight, ClinicalTrials.gov, WHO ICTRP, Ovid MEDLINE, and relevant grant databases) identified drugs, supplements, and biologics targeting the maternal gut microbiome. Probiotic candidates were matched against key TPP criteria to identify promising options for future research. Main outcome measures Stakeholder consensus (≥75% agreement) on TPP variables and identification of high-potential probiotic candidates. Results The TPP met consensus for most of the 20 variables: 16 for minimum and 14 for optimal targets. Interviews raised issues concerning indication, target population, diagnostic requirements, and efficacy outcomes. Of 38 candidates identified in the maternal microbiome pipeline (2000-2023), eight were probiotics, with one high-potential candidate (Vivomixx) and two medium-potential candidates (Lactobacillus spp. and Bifidobacterium spp.) identified. Conclusions This study produced the first TPP and pipeline analysis for maternal gut microbiome interventions, identifying probiotics with higher potential. Few candidates reached late-phase research, highlighting the need for efficacy trials.